2022
DOI: 10.1007/s00109-022-02279-z
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of hepatic CLOCK by PPARα is involved in inhibition of NAFLD

Abstract: This work aimed to investigate the role of nuclear factor peroxisome proliferator-activated receptor α (PPARα) in modi cation of circadian clock and their relevance to development of nonalcoholic fatty liver disease (NAFLD). Both male wild-type (WT) and Pparα-null (KO) mice treated with high-fat diet (HFD) were used to explore the effect of PPARα and lipid diet on the circadian clock. PPARα humanized (hPPARα) mice were treated with PPARα agonist feno brate to reveal the hPPARα-dependence of circadian locomotor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…On the other hand, the weight gain of the KO mice fed with a HFD was far less than that in the WT group, which was consistent with previous results. 25,26 Moreover, a HFD is typically associated with insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the weight gain of the KO mice fed with a HFD was far less than that in the WT group, which was consistent with previous results. 25,26 Moreover, a HFD is typically associated with insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the weight gain of the KO mice fed with a HFD was far less than that in the WT group, which was consistent with previous results. 25,26 Moreover, a HFD is typically associated with insulin resistance. We conducted an OGTT and found that both the WT and KO mice fed with a HFD showed impaired glucose tolerance, indicating that PPARα null mice are not protected from the effects of the HFD.…”
Section: Discussionmentioning
confidence: 99%